2016
DOI: 10.1038/ijo.2016.231
|View full text |Cite
|
Sign up to set email alerts
|

Obese individuals with more components of the metabolic syndrome and/or prediabetes demonstrate decreased activation of reward-related brain centers in response to food cues in both the fed and fasting states: a preliminary fMRI study

Abstract: It remains unknown whether obese individuals with more components of the metabolic syndrome and/or prediabetes demonstrate altered activation of brain centers in response to food cues. We examined obese prediabetics (n=26) vs. obese nondiabetics (n=11) using fMRI. We also performed regression analyses on the basis of the number of MetS components per subject. Obese individuals with prediabetes have decreased activation of the reward-related putamen in the fasting state and decreased activation of the salience-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…Each block was presented in a counterbalanced order and interspersed with periods of visual fixation. As previously described, food desirability was confirmed in a previous study and visual appearance of food images was matched for visual properties …”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Each block was presented in a counterbalanced order and interspersed with periods of visual fixation. As previously described, food desirability was confirmed in a previous study and visual appearance of food images was matched for visual properties …”
Section: Methodsmentioning
confidence: 96%
“…Participants viewed food and non‐food cues within a 3‐Tesla GE MR750 scanner at BIDMC while fasting, using a GE 32‐channel head array coil with a protocol similar to our previous publications . First, a T1‐weighted Magnetization Prepared Rapid Gradient Echo (MPRAGE) structural MR image was acquired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger portions of low-nutrient, high-caloric, palatable food consumed at irregular meal patterns by sedentary individuals are all factors promoting obesity (123). With the use of functional MRI (fMRI), internal factors including post-prandial decreased activation in rewardrelated putamen and salience-and reward-related insula in fasting subjects with obesity and prediabetes are hypothesized to underle caloric intake, which leads to these cnditioms (124). Altogether, these environmental and central mechanisms in combination with genetic, epigenetic and other mechanisms create a complex disease in need of effective therapies.…”
Section: :2 R65 Reviewmentioning
confidence: 99%
“…One study comparing BMI‐matched individuals with and without type 2 diabetes found that those with diabetes had relatively greater responsivity in emotion‐ and reward‐processing regions . Another more recent study observed relatively decreased reward‐processing activity for individuals with more components of metabolic syndrome and/or prediabetes . The same group found that, among individuals with diabetes, those with obesity demonstrated less activation in salience and reward‐related regions when fasted .…”
Section: Introductionmentioning
confidence: 99%